Pengelolaan Perbenihan Nilam Untuk Mencegah Penyebaran Penyakit Budok (Synchytrium pogostemonis) - WAHYUNO, WAHYUNO (Puslitbang Perkebunan, 2010)
ABSTRAKTanaman nilam (Pogostemon cablin) adalah tanaman penghasil minyak patchouli yang banyak diperlukan dalam industri parfum. Indonesia merupakan negara penghasil minyak nilam terbesar di dunia. Tanaman nilam telah tersebar luas di 12 propinsi di Indonesia, dengan penghasil utama propinsi Nanggroe Aceh Darusalam, Sumatera Utara, Sumatera Barat, Bengkulu, Jawa Barat dan Jawa Tengah. Tanaman nilam bukan tanaman asli Indonesia, jarang membentuk bunga, dan keragaman genetik yang ada di Indonesia sempit. Perbanyakan secara vegetatif dengan menggunakan setek pucuk atau setek batang merupakan cara perbanyakan nilam yang utama di Indonesia. Kekeringan dan gangguan OPT merupakan kendala yang banyak dijumpai di sentra produksi nilam. Akhir-akhir ini penyakit budok yang disebabkan oleh cendawan Synchytrium pogostemonis banyak ditemukan di sentra produksi nilam di Indonesia. Usaha untuk mengembangkan teknologi pengendalian terhadap S. pogostemonis sedang dilakukan dalam dua tahun terakhir ini. Karakteristik S. pogostemonis yang mempunyai struktur bertahan yang kuat dan mudah tersebar melalui benih nilam menjadi perhatian dalam usaha menekan kehilangan hasil akibat serangan S. pogostemonis. Pengelolaan perbenihan yang tepat merupakan cara yang paling efektif untuk menekan penyebaran S. pogostemonis dan pencemaran ke daerah penanaman nilam lainnya, diikuti dengan sertifikasi perbenihan dan pemantauan lalulintas benih.Kata kunci: Penyakit budok, Pogostemon cablin,Synchytrium pogostemonis, perbenihan, penyebaran ABSTRACTNursery Management of Patchouli for Inhibit Synchytrium pogostemonis DistributionPatchouli (Pogostemon cablin) is important patchouli oil producing plant that mostly needed for parfume industries. Indonesia is the bigest patcholi oil producing country. The plant is widely cultivated in Indonesia over 12 provincies, with the main producer areas mainly in Nanggroe Aceh Darusalam, North Sumatera, West Sumatera, Bengkulu, West Java and Central Java. The patchouli is not Indonesia origin, and sexual reproduction structure is rarely formed in Indonesia. Therefore the genetic diversity of the patchouli in Indonesia is narrow. Young vein cutting and stem cutting are common mass propagation method for this plant in Indonesia. Drought and the occurennce of insect pests and diseases are the main constraint in patchouli cultivation in Indonesia. Recently, a disease namely budok caused by Synchytrium pogostemonis an obligate plant parasite fungus is reported widely distributed in patchouli cultivation centre areas in Indonesia. Attempts to find effective control measures of the disease has just been conducted in the last two years. Thus only limited informations on the fungus has been obtained up to present. The fungus has winter spore state that leads the fungus organ persist in the soil, and still viable for a long period. The existence of the winter spore should be main focus in reducing yield lost due to S. pogostemonis infection. Proper in seedling preparation and handling are considered the best way to inhibit S. pogostemonis distribution and contaminating budok disease free areas. Improvement in pogostemon seedling preparation procedure, and statutory in seedlings transportation are considered the best way to delimit of budok disease impact in the present time; then followed by seedling certification, and stricly quarantine monitoring also supose to be intensively carried out immediately.Keywords: Wart disease, Pogostemon cablin, Synchy-trium pogostemonis, nursery, spreading